Evaluation of clinical abdominal scoring system for predicting outcomes of blunt abdominal trauma - Nico Odolf Yordanius; I Ketut Wiargitha; Nyoman Golden; I Wayan Periadijaya; I Wayan Sudarsa; I Wayan Niryana (Faculty of Medicine, Universitas Trisakti, 2023)
Background Trauma has been called the neglected disease of modern society and the most common cause of death under 45 years. Determining the optimal prospective course of action may be aided by the adoption of a scoring system to evaluate urgent laparotomy intervention. A quick and easy technique to identify whether there are any intra-abdominal injuries is to use the clinical abdominal scoring system (CASS). The objective of this study was to evaluate CASS in predicting the outcomes in patients with blunt abdominal trauma (BAT). Methods A retrospective observational study was conducted involving 80 patients with suspected BAT that arrived at the emergency department. All patients with suspected BAT were scored using CASS and radiological investigations that were done in the ED. The decision to proceed with the surgery would be made if the patient had CASS >12 and/or if the radiological investigation showed features of BAT such as air under the diaphragm. Results Mean CASS score was 10.28 ± 1.340. The majority of the subjects (75 or 93.5%) had successful laparotomies, whereas only five (6.3%) had unsuccessful ones. Injuries to the spleen (42.6%), and liver (32%), combined injuries to the spleen and liver (2.6%), intestine (16%), pancreas (1.3%), bladder (4%), and kidneys (1.5%) were all found in positive laparotomies. The CASS has specificity of 60%, sensitivity of 80%, PPV 96.7%, and NPV 16.6%. Conclusions According to our data results, The CASS has a poor ability to predict the need for laparotomy in cases of blunt abdominal injuries as it shows low specificity.